PENGARUH KEAHLIAN PENGGUNA, KESESUAIAN TUGAS DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PENGGUNA SISTEM INFORMASI AKUNTANSI (SIA) - I Gusti Agung Ayu Tri Riyantini; Ni Putu Yeni Yuliantari (UNHI Press, 2021)
This research is to find out the influence of user expertise, suitability of tasks and organizational culture on the performance of employees of accounting information systems (SIA).This research was conducted BPR in Mengwi Sub-District, Badung, with the samples are 76 respondents. The sample determination method is non probability sampling with purposive sampling, the data analysis technique used is multiple linear regression analysis, determination coefficient (R2), F test, t test. The results showed that User expertise had a positive and significant effect on employee performance variables. The task suitability has a positive and significant effect on employee performance variables. The organization culture has a positive and significant effect on employee performance variables.